Metabolic tools for identification of new mutations of enzymes engaged in purine synthesis leading to neurological impairment - Krijt, Matyáš; Součková, Olga; Barešová, Veronika; Škopová, Václava; Zikánová, Marie (Folia biologica (Praha), 2019)
The cellular pool of purines is maintained by de novo purine synthesis (DNPS), recycling and degradation. Mutations in genes encoding DNPS enzymes cause their substrates to accumulate, which has detrimental effects on cellular division and organism development, potentially leading to neurological impairments. Unspecified neurological symptoms observed in many patients could not be elucidated even by modern techniques. It is presumable that some of these problems are induced by dysfunctions in DNPS enzymes. Therefore, we determined the concentrations of dephosphorylated DNPS intermediates by LC-MS/MS as markers of yet unpublished mutations in PFAS and PAICS genes connected with dysfunctions of carboxylase/phosphoribosylaminoimidazolesuccinocarboxamide synthase (PAICS) or phosphoribosylformylglycinamidine synthase (PFAS). We determined the criteria for normal values of metabolites and investigated 1,447 samples of urine and 365 dried blood spots of patients suffering from various forms of neurological impairment. We detected slightly elevated aminoimidazole riboside (AIr) concentrations in three urine samples and a highly elevated 5-formamidoimidazole-4-carboxamide riboside (FGAr) concentration in one urine sample. The accumulation of AIr or FGAr in body fluids can indicate PAICS or PFAS deficiency, respectively, which would be new disorders of DNPS caused by mutations in the appropriate genes. Measurement of DNPS intermediates in patients with neurological symptoms can uncover the cause of serious cellular and functional impairments that are otherwise inaccessible to detection. Further genetic and molecular analysis of these patients should establish the causal mutations for prenatal diagnosis, genetic consultation, and reinforce the DNPS pathway as a therapeutic target.
Keywords: Urine; test suché kapky krve; metabolom; Nervous System Diseases; lidé; Metabolome; moč; Limit of Detection; nemoci nervového systému; limita detekce; metabolomika; mutace; puriny; Dried Blood Spot Testing; Humans; Metabolomics; Mutation; Purines